The Relationship between Banks’ Income Smoothing and Loan Loss Provision, as well as the Performance of Bank - MU, CHENXUAN (2017)
In this paper, I am desire to explore the positive relationship between income smoothing and the performance of bank. This aim is going to achieve by estimating two relationships. One is the relationship between income smoothing and loan loss provision, and another is the relationship between loan loss provision and performance of banks. And through using the Generalized Method of Moments (GMM) model, I could make the conclusion that income smoothing is positive related with banks’ loan loss provision, but not to a great extent. And through estimating by the Stochastic Frontier Analysis (SFA) model, I could make the conclusion that loan loss provision and the performance of bank, which is represented by cost inefficiency in this paper, have a positive relationship. However, this result is not suitable with the real situation. Therefore, the original anticipation has not been achieved.